Epstein-Barr Virus Positive Mucocutaneous Ulceration: A case report - Hiraa Javed; Parkash L. Ramchandani (Elsevier, 2021)
Epstein-Barr Virus Positive Mucocutaneous Ulceration (EBV-MCU) is a rare condition on the spectrum of lymphoproliferative disorders (LPDs). It was first described in 2010 as unifocal mucosal or cutaneous ulcer that often occurs in elderly patients or who show evidence of immunosuppression. With its non-specific clinical appearance and histological characteristics of EBV-positive atypical B-cells, EBV-MCU appears to be at risk of misdiagnosis. Avoiding unnecessary treatments by being able to distinguish EBV-MCU from other EBV-associated LPDs as well as conditions that display a similar clinical appearance, would reduce any burden and harm to patients.